The Value Issue of Business: The Responsibility of the Businessman - Elbing, Alvar O. (Academy of Management Journal, 1970)
In the arena of today's social value problems, the businessman is accused and victimized by his own professional rationale?a rationale derived from traditional economic theory. This rationale, unlike that of other professions (e.g., law or medicine), does not consist of an ideal value standard, but rather is an abstract caricature of self-interest. This rationale must be abandoned for a social (rather than a purely economic) model, one which realistically clarifies the nature of the social co-responsibility inherent in the businessman' s professional role.